Synthesis of Allenylphosphonates through Cu(I)-Catalyzed Coupling of Terminal Alkynes with Diazophosphonates - Wu, Chenggui; Ye, Fei; Wu, Guojiao; Xu, Shuai; Deng, Guisheng; Zhang, Yan; Wang, Jianbo (Synthesis, 2016)
Through the Cu(I)-catalyzed coupling of diazophosphonates with terminal alkynes, an efficient method for the synthesis of allenylphosphonates has been developed. Simple and inexpensive CuI is used as the catalyst and the reaction is conducted under mild conditions.
Keywords: diazophosphonate; allene; cross-coupling; carbene; copper